2022
DOI: 10.1177/1071181322661165
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the Road: How Human Drivers Interact with Autonomous Vehicles on Highways

Abstract: With more autonomous vehicles (AVs) being tested or deployed on public roads, human-driven vehicles (HVs) have to share the road with AVs. However, human drivers may not interact AVs the same way as they interact with HVs. Very few studies have investigated drivers’ behaviors when sharing the road with AVs. Based on a real-world dataset, our study explored drivers’ interactions with AVs in two types of events on highway, i.e., car-following event and car-passing event. The results show that, compared to intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It seems that when proceeding straight, human drivers were less capable of anticipating the motion of an ADS-controlled vehicle compared with when there was lateral movement of human-driven vehicles. Previous research has observed a smaller time-to-collision when human drivers were following an ADS-controlled vehicle in mixed traffic compared with when following a human-driven vehicle (12). It might be possible that, when proceeding straight, the front view of the following driver is more likely to be blocked by the lead vehicle; if the ADS-controlled vehicle is not pre-active to the incidents ahead, the time budget left for the following vehicle to respond will be limited.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It seems that when proceeding straight, human drivers were less capable of anticipating the motion of an ADS-controlled vehicle compared with when there was lateral movement of human-driven vehicles. Previous research has observed a smaller time-to-collision when human drivers were following an ADS-controlled vehicle in mixed traffic compared with when following a human-driven vehicle (12). It might be possible that, when proceeding straight, the front view of the following driver is more likely to be blocked by the lead vehicle; if the ADS-controlled vehicle is not pre-active to the incidents ahead, the time budget left for the following vehicle to respond will be limited.…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, from the start of the DMV program (2014) to Nov. 2018, rear-end collisions were 61.1% of all ADSinvolved crashes in the DMV dataset (8). Similarly, research based on the Waymo open dataset also revealed that, compared with human driven vehicles, ADS-driven vehicles led to smaller time-to-collision of following vehicles (12,22). The research by Song et al provided further details of ADS-involved rear-end crashes-it was found that the most representative temporal pattern of ADSinvolved crashes was ''collision following autonomous vehicle stopping'' (11).…”
Section: Patterns Of Ads-related Crashesmentioning
confidence: 94%
See 1 more Smart Citation